River of hope : forging identity and nation in the Rio Grande borderlands - Valerio-Jiménez, Omar S. (Omar Santiago), 1963- (Duke University Press, 2013)
In River of Hope, Omar S. Valerio-Jiménez examines state formation, cultural change, and the construction of identity in the lower Rio Grande region during the eighteenth and nineteenth centuries.